Penerapan teknik guided imagery untuk menurunkan tingkat kejenuhan belajar siswa - Margawati Margawati; Nurhidayatullah D; Salmiati Salmiati (Orien: Cakrawala Ilmiah Mahasiswa, 2022)
the aims of the study were to determine: a) the description of the level of learning saturation in SMAN 1 Pangkep, b) the guided imagery technique can reduce the level of student learning saturation in SMAN 1 Pangkep. This research uses a quantitative approach, the type of research is pre experimental designs. The research design used was a pretest-posttest control group design for 12 research samples which were class XI students at SMAN 1 Pangkep, the sampling used was proportional random sampling. This study uses data collection techniques through questionnaires and observations. Data analysis used descriptive statistical analysis using t test. The results of this study indicate that: a) the level of student learning saturation before being given guided imagery techniques is in the high category, and b) the application of guided imagery techniques can reduce the level of student learning saturation at SMAN 1 Pangkep.